Integrating carbon nanotubes and lipid bilayer for biosensing - Huang, Yinxi (2011)
Membrane proteins, which are the target of most drugs, are implicated in many critical cellular functions such as signal transduction, bioelectricity, exocytosis and endocytosis. Therefore, developing techniques to investigate the functions of membrane proteins is obviously important. Here, we have developed a novel system by integrating artificial lipid bilayer (biomimetic membrane) with single-walled carbon nanotube networks (SWNT-net) based field-effect transistor (FET), and demonstrated that such hybrid nanoelectronic biosensors can specifically and electronically detect the presence and dynamic activities of ionophores (specifically, gramicidin and calcimycin) in their native lipid environment. This technique can potentially be